2020
DOI: 10.17582/journal.pjz/20190204150214
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nonlinear Functions using Partial Growth Data at Different Lengths of Growth Period in Awassi Lambs

Abstract: Photoperiod and shelter have direct or indirect effects on phenotypic traits expression in different fish species. The present study was, therefore, intended to explore whether these light and shelter could influence some phenotypic traits of African catfish larvae under laboratory condition. Newly hatched larvae were stocked in plastic aquaria (10L) at a rate of 5 individuals/L and reared for one month under four treatments such as 24h light (24L), 24 h dark (24D), 12h light and 12h dark with PVC (12DL_PVC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Modelling animal growth with non‐linear models allows the prediction of future body weight at any age (Bathaei & Leroy, 1996; Tekel et al., 2005). Previous reports of genetic variation among estimates of growth parameters suggested that these parameters could serve as selection criteria in breeding programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Modelling animal growth with non‐linear models allows the prediction of future body weight at any age (Bathaei & Leroy, 1996; Tekel et al., 2005). Previous reports of genetic variation among estimates of growth parameters suggested that these parameters could serve as selection criteria in breeding programmes.…”
Section: Discussionmentioning
confidence: 99%
“…( 2013 ) determined that the MMF model provided the best fit to body weight data of all male and female Mengali sheep. The Logistic model has been demonstrated to have the best goodness of fit for Moghani (Ghavi Hossein‐Zadeh, 2017 ), Santa Ines (da Silva et al., 2012 ), Norduz (Daskiran et al., 2010 ) and Awasi (Tekel et al., 2005 ) sheep breeds. The Brody model was selected as the most accurate representation of data for Hemsin (Kopuzlu et al., 2013 ), Baluchi (Bahreini Behzadi et al., 2014 ) and Mehraban (Hojjati & Ghavi Hossein‐Zadeh, 2017 ) lambs.…”
Section: Discussionmentioning
confidence: 99%
“…Bu dönemde kısa zamanda oransal olarak hızlı bir gelişme olmaktadır. Eğrinin üst kısmındaki bükülme, bütün dokuların büyüme ve gelişmesini durdurduğunu ya da yavaşladığını göstermektedir (7)(8)(9).…”
unclassified